If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8v + -4 = -4 + -6v Reorder the terms: -4 + -8v = -4 + -6v Add '4' to each side of the equation. -4 + 4 + -8v = -4 + 4 + -6v Combine like terms: -4 + 4 = 0 0 + -8v = -4 + 4 + -6v -8v = -4 + 4 + -6v Combine like terms: -4 + 4 = 0 -8v = 0 + -6v -8v = -6v Solving -8v = -6v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '6v' to each side of the equation. -8v + 6v = -6v + 6v Combine like terms: -8v + 6v = -2v -2v = -6v + 6v Combine like terms: -6v + 6v = 0 -2v = 0 Divide each side by '-2'. v = 0 Simplifying v = 0
| 7+5x+5=-13 | | k=10 | | 16x=12x-2x^2 | | 16=-8n-8n | | 95=5(2n+6)+5 | | (3-6q)=-18 | | 2(9S+10)-35=3(5S+6)-23 | | 16=3+30t-16t^2 | | 1.8(k-273.15)+32=f | | 36=9h | | 0.6(x+10)+0.6x=42 | | 16=30t-16t^2 | | 9(x)/13=36 | | 9(x)/13=13 | | y^2-3y+9= | | 0.15x+.05(16-x)=.10(16) | | 9c-(2m+1)=20 | | 12(3x+4)-7(2x-3)=2x-31 | | 6x-18=11x-28 | | -2.9+(-5.2)= | | 26=54t+-5t^2 | | g-5/3=5/3 | | w^2-2w-63= | | 65=65-10t-16t^2 | | 2x^2-2x= | | 18=4+38t-16t^2 | | 5x+2=2x+50 | | 23y-6y+y-8=1 | | 6y+9=5y-7 | | 2x+8x-5=1 | | 28-(x+6)=5x-2 | | 4x-15=85 |